2003
DOI: 10.1161/01.cir.0000047525.58618.3c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of AGI-1067 and Probucol After Percutaneous Coronary Interventions

Abstract: Background— AGI-1067, a metabolically stable modification of probucol, is an equipotent antioxidant to probucol but is pharmacologically distinct. In a multicenter trial, we studied whether AGI-1067 reduces restenosis assessed by intravascular ultrasound (IVUS) after percutaneous coronary intervention (PCI) compared with placebo and probucol used as a positive control. Methods and Results— Two weeks before PCI, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 173 publications
(119 citation statements)
references
References 24 publications
4
112
0
3
Order By: Relevance
“…Probucol is an anti-oxidant and lipid-reducing drug that has been in clinical use during the past few decades for the prevention and treatment of cardiovascular diseases. In experimental and clinical studies, probucol has been reported to reduce intimal proliferation following balloon injury in animals [12,13] and to inhibit restenosis after coronary angioplasty with [14] and without [15] stent in humans. Probucol also dramatically retards atherosclerosis in hyperlipidemic animals [16][17][18] .…”
Section: Original Articlementioning
confidence: 99%
“…Probucol is an anti-oxidant and lipid-reducing drug that has been in clinical use during the past few decades for the prevention and treatment of cardiovascular diseases. In experimental and clinical studies, probucol has been reported to reduce intimal proliferation following balloon injury in animals [12,13] and to inhibit restenosis after coronary angioplasty with [14] and without [15] stent in humans. Probucol also dramatically retards atherosclerosis in hyperlipidemic animals [16][17][18] .…”
Section: Original Articlementioning
confidence: 99%
“…Patients were treated for two weeks before and four weeks after PCI in this phase 2 trial. The minimal lumen area at the site of PCI on follow-up intravascular ultrasound (IVUS) was on average 2.66 mm 2 in the placebo group, 3.69 mm 2 in the probucol group, 2.75 mm 2 in the AGI-1067 70 mg group, 3.17 mm 2 in the AGI-1067 140 mg group and 3.36 mm 2 in the AGI-1067 280 mg group (P<0.05 for AGI-1067 280 mg and probucol versus placebo) (39). There was also a significant dose-response relationship of AGI-1067 for the primary end point (P=0.02, Figure 1).…”
Section: Cart-1mentioning
confidence: 99%
“…Volumetric (three-dimensional) changes of nonintervened coronary reference segments, away from the PCI site, were also evaluated with IVUS in a post hoc analysis in CART-1 (39). The mean change in lumen volume (follow-up minus baseline) in the reference segments was -5.3 mm 3 in the placebo group, -0.2 mm 3 in the probucol group and -2.4 mm 3 in the AGI-1067 70 mg group, but was +3.5 mm 3 in the AGI-1067 140 mg group and +1.8 mm 3 in the AGI-1067 280 mg group (P=0.05 for AGI-1067 140 mg versus placebo; P=0.077 for doseresponse relationship).…”
Section: Cart-1mentioning
confidence: 99%
“…The Aggressive Reduction of Inflammation Stops Events (ARISE) trial is testing a synthetic antioxidant that is structurally related to probucol (30) in more than 6000 patients with recent acute coronary syndromes. In addition, several other anti-inflammatory compounds are being tested, including those that target the leukotriene pathway and phospholipase A2 and serine protease inhibitors (31)(32)(33).…”
Section: Other Pharmacological and Nonpharmacological Approachesmentioning
confidence: 99%